2021
DOI: 10.1088/1755-1315/752/1/012023
|View full text |Cite
|
Sign up to set email alerts
|

The Existence and Population Dynamic of New Fall Armyworm Species Spodoptera frugiperda J. E. Smith (Lepidoptera: Noctuidae) in Yogyakarta, Indonesia

Abstract: Fall Armyworm Spodoptera frugiperda (Lepidoptera: Noctuidae) is a new pest in Indonesia that attacks corn plants. S. frugiperda larvae damage by eating the leaves to the growing point which can result in yield loss from 55 to 100%. This pest reportedly attacked corn plantations at the beginning of 2019 then spread almost throughout Indonesia. This study aims to study the distribution and population dynamic of S. frugiperda in Yogyakarta, Indonesia. Preliminary research was conducted in Sleman and Bantul regenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 8 publications
1
6
0
1
Order By: Relevance
“…The advantage of Coccinellidae members who prey on aphids on corn plants, besides getting prey in the form of aphids, they can also prey on the first and second instar larvae of S. frugiperda found on these corn plants. This is in accordance with research from Nurkomar, et al [3] who stated that apart from preying on aphids, predatory Coccinellidae found on corn plants also prey on the early instar larvae of S.…”
Section: Insect Predator Of S Frugiperda In Sleman and Gunungkidul Re...supporting
confidence: 93%
See 1 more Smart Citation
“…The advantage of Coccinellidae members who prey on aphids on corn plants, besides getting prey in the form of aphids, they can also prey on the first and second instar larvae of S. frugiperda found on these corn plants. This is in accordance with research from Nurkomar, et al [3] who stated that apart from preying on aphids, predatory Coccinellidae found on corn plants also prey on the early instar larvae of S.…”
Section: Insect Predator Of S Frugiperda In Sleman and Gunungkidul Re...supporting
confidence: 93%
“…The corn armyworm (Spodoptera frugiperda) is an insect native to the United States that has spread to the Asian continent, including Indonesia. Spodoptera frugiperda was originally found in the Pasaman area, West Sumatra [1] and has spread to Bandung, Garut, Sumedang [2] to Sleman, Gunungkidul, Bantul, Yogyakarta [3]. Armyworm caterpillars have several host plants, especially from the Graminae group such as corn, rice [4] cotton [5] and sorghum [6].…”
Section: Introductionmentioning
confidence: 99%
“…FAW can attack corn plants during the vegetative and generative periods. In the vegetative period, FAW can attack corn plants from 10 days after planting (dap) to 45 dap with varying attack levels and even some reached 100% [9][10][11][12][13][14]. The different levels of attack on corn plants are due to the age of the plants and the variety of plants planted.…”
Section: Introductionmentioning
confidence: 99%
“…Spodoptera frugiperda was first detected attacking corn farms in Pasaman, West Sumatra, Indonesia [1]. After its first reported entry into Indonesia, S. frugiperda attacks started to be reported in several other regions, such as Java [2][3][4][5][6][7] and eastern Indonesia [8], [9]. Since attacks have been reported in almost all areas, it can be suspected that S. frugiperda may have long been developed in Indonesia, but this is not explicitly known [10].…”
Section: Introductionmentioning
confidence: 99%
“…Maharani et al (2019) reported a low population of S. frugiperda in parts of West Java and Yogyakarta[5]. Meanwhile,Trisyono et al (2019) and Arfan et al (2020) reported high levels of S. frugiperda infestation in Lampung and Palu, respectively.…”
mentioning
confidence: 98%